Descriptions of the Patagonian species of the subgenus Trichohelea of Forcipomyia, with a key to the Neotropical species (Diptera: Ceratopogonidae) - Marino, Pablo Ignacio (2004)
The following two new species of Forcipomyia (Trichohelea) collected in the Nothofagus patagonian forest are described and illustrated: F. (T.) sayhuequei from the province of Chubut in Argentina and Llanquihue in Chile, and F. (T.) tehuelche from the Argentinean province of Santa Cruz. Based on the examination of the types, the previously known species Lasiohelea shannoni Ingram and Macfie is recognized as a junior synonym of Forcipomyia limnetis Ingram and Macfie, and the species is redescribed and illustrated. A key to recognition of females and males of the 14 Neotropical species of the subgenus is included.